Habitat complexity influenced mixed-species bird flock composition and occurrence in highlands - Muñoz, Pablo; Sandoval, Luis (Revista de Biología Tropical, 2025)
Introduction: Mixed-species bird flocks are groups that change rapidly throughout the day, influenced by factors such as resource availability, vocalizations, and habitat complexity. Habitat complexity can either enhance or limit interspecific interactions by increasing the number of species or individuals that interact. However, variations in habitat structure are often overlooked when studying mixed-species flock composition, leading to incomplete or unrealistic interpretations of factors influencing flock composition. Objective: This study aims to investigate the relationship between the composition and occurrence of mixed-species bird flocks and the habitat complexity of a highland forest in Costa Rica. Methods: We conducted this study along a 5.5 km transect in the highland area of Braulio Carrillo National Park in Heredia, Costa Rica (10°05’ N & 84°04’ W; 2100 m a.s.l.) from March to December 2019. Mixed-species flocks were surveyed twice weekly from 06:00 to 11:00 h. Habitat complexity was assessed using 16 plots (10x10 m) distributed across the study area to capture most of the habitat variation. We estimated the probability of occurrence at different habitat types for mixed-species flock that vary in sizes using kernel density estimation in QGIS. Results: A total of 34 species were recorded across 125 mixed-species flocks, categorized into 50 small-sized, 46 medium-sized, and 30 large-sized flocks. Flock sizes were associated with different habitat characteristics. A positive association was found between higher canopy and understory cover, tree quantity, and diameter at breast height (DBH) with species composition and abundance in large-sized flocks, but not in medium- and small-sized flocks. Conclusion: While the overall presence of mixed-species flocks was not limited by habitat structure, their size and composition were significantly associated with habitat.